(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
RRDN Trucking is a company that strategizes on how to gain a dominant position in the trucking industry. The primary purpose of RRDN Trucking is to deliver goods and supplies to their destination safely, professionally, and in a timely manner. RRDN Trucking hoped to establish more units in each city to speed the delivery of valuables and goods to various locations in the Philippines while maintaining the value of consumers and their bottom line. The researchers chose this topic to learn more about improving service performance in RRDN Trucking Services: An Assessment. This study used a descriptive research design. The study’s respondents were fifty (50) customers of RRDN trucking service. This study utilized the purposive sampling technique. The data was totaled and analyzed using frequency, percentage, and a weighted mean. As a result of the study, after the researchers conducted an online survey with 50 respondents from customers, most are 32 to 37 years old, males, or get services monthly. Most get serviced within 1 to 24 hours. Based on the information gathered, this research could help RRDN trucking service improve its service by considering the recommendation. These include, when it comes to service recovery, being prompt and efficient in responding and resolving issues, making sure the follow-up is prompt, and not letting too much time pass before checking in on the customer. They should be able to plan and strategize company policies and operations so that every aspect of the business is well organized to reduce the chances of service failure. Also, ensure services run efficiently to meet the promised delivery schedule and dates. The data results were more focused on improvement factors to consider the customer’s feedback and attain customer satisfaction.